2019
DOI: 10.35333/jrp.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and cytotoxic activity of resveratrol-gold nanoparticles conjugated to folic acid against MCF-7 cell line

Abstract: The potential benefits of resveratrol (Trans-3, 5, 4'-trihidroxy stilbene) as an anti-cancer are lowered because of it's low aquous solubility, instability and low bioavailability. Recent progresses in nanoparticle technology offer a promising loophole to solve many problems in developing theurapetic agents. The ability of a nanocarrier to selectively bring drug substances to the site of a tumor solely based on passive targeting can be enhanced by coupling a ligand to the surface of the nanocarrier knowingly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…This indicated that RSV-Au-PEG-FA nanoparticles needs higher concentration than free RSV to cause toxic effect on HeLa cells. This is contrary to previous studies in which RSV in nanoparticles form were generally more toxic than free RSV [31,40].…”
Section: Cytotoxicity Studycontrasting
confidence: 99%
See 1 more Smart Citation
“…This indicated that RSV-Au-PEG-FA nanoparticles needs higher concentration than free RSV to cause toxic effect on HeLa cells. This is contrary to previous studies in which RSV in nanoparticles form were generally more toxic than free RSV [31,40].…”
Section: Cytotoxicity Studycontrasting
confidence: 99%
“…This might be caused by linker type used was forming strong and stable bond even in cellular environment which inhibited the release of RSV from RSV-Au-PEG-FA nanoparticles. In previous study, polyvinyl alcohol was used as linker and nanoparticles formed needed lower concentration than free RSV to cause toxic effect on cancer cells [40].…”
Section: Cytotoxicity Studymentioning
confidence: 99%